2008
DOI: 10.1038/eye.2008.198
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate: an option for preventing the recurrence of acute anterior uveitis

Abstract: Aims To evaluate the efficacy of methotrexate (MTX) in preventing the recurrence of acute anterior uveitis (AAU). Methods This prospective, open, longitudinal study included patients from June 2002 to March 2005 who had either three or more episodes of AAU in the previous year, or a recurrence of AAU within 3 months before starting the trial. We excluded uveitis of infectious origin, masquerade syndromes, and patients with contraindications to MTX. The response criteria were defined as an absence of symptoms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 15 publications
2
30
0
1
Order By: Relevance
“…Data, which are usually anecdotal, also support the concept that a monoclonal antibody to TNF is more effective than a soluble receptor for treating uveitis in most patients [21]. Sulfasalazine [22,23], methotrexate [24], and perhaps oral nonsteroidals anti-inflammatory drugs [25] can also help to reduce the frequency or intensity of attacks of uveitis in B27-positive patients. These drugs have less cost and less risk than biologic therapies.…”
Section: Prevention Of Uveitismentioning
confidence: 85%
“…Data, which are usually anecdotal, also support the concept that a monoclonal antibody to TNF is more effective than a soluble receptor for treating uveitis in most patients [21]. Sulfasalazine [22,23], methotrexate [24], and perhaps oral nonsteroidals anti-inflammatory drugs [25] can also help to reduce the frequency or intensity of attacks of uveitis in B27-positive patients. These drugs have less cost and less risk than biologic therapies.…”
Section: Prevention Of Uveitismentioning
confidence: 85%
“…In addition, the group with AAU was receiving less methotrexate because most of them were AS patients, and this medication has no proven effect in patients with predominance of axial involvement. The value of methotrexate in cases of AAU and SpA is controversial and based on small studies, 15 since most studies on uveitis have not classified the uveitis treatment according to etiology. 16,17 A negative relationship was found between skin disease (psoriasis) and the presence of AAU.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have suggested that sulfasalazine (SSZ) may prevent recurrence of AU in patients with AS5 6 and some positive data also exist for methotrexate (MTX)7 and non-steroidal anti-inflammatory drugs (NSAID) 8. Treatment with tumour necrosis factor-α inhibitors (TNFi) has also repeatedly been shown to reduce the occurrence of AU in patients with AS,9–11 with reports including both reduced rates compared with placebo-treated patients,10 12 13 and compared with rates pre-TNFi-treatment 11 14.…”
Section: Introductionmentioning
confidence: 99%